Teamwork: Strategies for a successful robotic program. Issue 6 (30th November 2015) - Swift, Lystra M.; Carlos, Grace; Beresford, Marcia; Patane, Michael; Enright, Olivia; Langone, Stephanie; Leitao, Mario M.; Laudone, Vincent
Abstract : Robotic surgery is performed through small incisions using surgical instruments attached to robotic arms. Each member of the team is instrumental in the overall success of the program.